Effects of Leafy Flexible Vegetation on Bed‐Load Transport and Dune Geometry - G. Artini; S. Francalanci; L. Solari; J. Aberle (Water Resources Research)
Abstract The development of sustainable river management strategies requires knowledge of the effect of vegetation on hydrodynamics and sediment transport. To date, the complex physical processes involving the combined effects of leafy flexible vegetation and mobile bedforms are not completely understood. Most sediment transport models have been developed for bare bed conditions so that their performance in the presence of leafy flexible vegetation remains unclear. On the other hand, recently developed models consider vegetated conditions but they typically account only for the presence of rigid cylinders and in some cases scour at their base. For this purpose, laboratory experiments were conducted with mobile dune bed conditions and artificial flexible plants with varying Leaf Area Index to investigate the effect of flexible vegetation on bed morphology and sediment transport. Sediment transport rates and bedform characteristics such as height, wavelength and celerity, were measured in specifically designed experimental runs. The collected data show that the presence of leafy vegetation alters bed morphology, tending to reduce the average dune wavelength and leading to the formation of complex 3D geometries. Bed‐shear‐stress‐based models for predicting sediment transport were verified to be valid under conditions of low vegetation roughness density. On the contrary, the collected data emphasize that the measured bed‐load transport rate increased in the presence of leafy flexible vegetation with higher frontal area. Recent bed‐load models for vegetated channels provide a better interpretation for dense leafy vegetation but are less effective when predominant effects related to dunes are present.